“I’m Going to Suffer Torture. I’m Going to Suffer Pain. I’m Going to Suffer the Hell of Temptation…” Boruta in the Novel of Kazimierz Gliński - Domagalska, Małgorzata (Diabeł Boruta w dawnej kulturze polskiej, 2021)
The purpose of this article is to analyze the novel of Kazimierz Gliński Boruta published in 1904. The most famous devil from Łęczyca does not resemble here the character known from earlier legends. He is not a devil, who gets bored sitting at the castle in Łęczyca and that is why he plays tricks on the nearby nobility. Boruta in the Gliński’s novel is an artist who in his songs resembles days of glory of Polish knights and explains the origin of evil. He is also a devil who is sentenced to tempting for the treason he committed against “the Spirit-King” Popiel. Boruta is also a devil – moralist who reveals people’s dark desires, he tempts human beings, but they have to choose what they will eventually do.